Using DEXA to diagnose impending atypical femoral fracture in an asymptomatic patient on long term bisphosphonates: A case report of a missed opportunity for fracture prevention - Ashraf Amin Ariff; Panagiotis Konstantinou; Michael Cuss; Charmaine Riley Nelson; Ahmed Hamed; Anastasios P. Nikolaides (Clinical Case Reports)
Key Clinical Message We report a patient who sustained an AFF (Atypical femoral fractures) after 15 years of bisphosphonate treatment. DEXA scans can be utilized to identify early evidence of AFF in asymptomatic patients up to 9 years before the development of an AFF.